PERENCANAAN PEMBANGKIT LISTRIK TENAGA MINI HIDRO PADA DAERAH NON-CAT DI DAS BEKASI - Diko Muhammad Abe; Rudi Setiyo Nugroho; Robert J. Kodoatie; Salamun Salamun (Jurnal Karya Teknik Sipil, 2015)
Mini Hydro Power Plant (MHPP) is a Hydro Power Plant that generates electrical energy within 100 KWH to1 MWH. MHPP on non-ground water in Bekasi watershed located on 6º28’16,66’’ S - 106º53’48,75’’ E for Bekasi Upstream Weir and 6º27’57,06’’ S - 106º53’39,75’’ E for the power house. Bekasi Upstream Weir is located on Cileungsi River stream and the power house is on Bantarjati Village, Kelapa Nunggal Sub-District, Bogor District, West Java Province. The MHPP planning first starts by analyzing the hydrology to get the flood discharge plan and dependable discharge. Structure planning for MHPP includes weir planning, intake building, settling basin, penstock, and power house. With 205 km2 total area of non-ground water in Bekasi watershed, Cileungsi River has a 962.30 m3/second flood discharge plan with 50 years repeating period and 2,5 m3/second dependable discharge. Power plant has a weir to elevate water level with 43.2 m effective width and 10 m crest height. This MHPP has 10 m head fall height and generates electricity 154.22 kwH with one turbine.